2013
DOI: 10.3892/ijo.2013.2231
|View full text |Cite
|
Sign up to set email alerts
|

S100A6 stimulates proliferation and migration of colorectal carcinoma cells through activation of the MAPK pathways

Abstract: The S100A6 protein, a member of the S100 protein family, is overexpressed in many tumors including colorectal carcinoma (CRC). Although recent studies showed that the elevated expression of S100A6 was associated with the stage and lymphatic permeation of CRC, little is known about whether and how S100A6 contributes to CRC development. Here we investigated the S100A6 expression in CRC tissues and cell lines, and explored the molecular mechanisms underlying the role of S100A6 in CRC development by examining cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
3
31
3
Order By: Relevance
“…This result confirms that p38/MAPK is a key signaling pathway by which S100A6 regulates the proliferation of NPC cells. This finding was different from an observation in colorectal carcinoma, in which S100A6 stimulated both p38 and ERK . The p38/MAPK signaling pathway is well known to play a critical role in the regulation of various cellular processes, and a growing body of evidence indicates the importance of p38/MAPK signaling in NPC progression.…”
Section: Discussioncontrasting
confidence: 93%
“…This result confirms that p38/MAPK is a key signaling pathway by which S100A6 regulates the proliferation of NPC cells. This finding was different from an observation in colorectal carcinoma, in which S100A6 stimulated both p38 and ERK . The p38/MAPK signaling pathway is well known to play a critical role in the regulation of various cellular processes, and a growing body of evidence indicates the importance of p38/MAPK signaling in NPC progression.…”
Section: Discussioncontrasting
confidence: 93%
“…Inspection of SS from neoHFFs treated with SW480‐Exos or SW620‐Exos revealed unique upregulation of protein S100‐A6 that is implicated in CAF and cancer cell proliferation and farnesyl‐diphosphate synthase (FDPS) that is implicated in proliferation . S100‐A6 belongs to the A group of the S100 protein family of calcium‐ binding proteins and is upregulated in tumor tissues including colon cancer tissues . Exogenous supplementation of S100‐A6 enhanced colon cancer cell proliferation in vitro and tumor growth in vivo through MAPK activation .…”
Section: Resultsmentioning
confidence: 99%
“…S100‐A6 belongs to the A group of the S100 protein family of calcium‐ binding proteins and is upregulated in tumor tissues including colon cancer tissues . Exogenous supplementation of S100‐A6 enhanced colon cancer cell proliferation in vitro and tumor growth in vivo through MAPK activation . FDPS is a key intermediate enzyme in the mevalonate pathway for lipid moieties synthesis that are critical for cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that S100 family can regulate tumor proliferation and metastasis via MAPK signaling pathway . In addition, S100A11 was reported to mediate tumor cell survival and malignant progression through activation of the P38 MAPK pathway .…”
Section: Resultsmentioning
confidence: 99%